The Difficult Decision Not to Prescribe Artificial Nutrition by Health Professionals and Family: Bioethical Aspects - Pereira, Andrea Z.; da Cunha, Selma Freire de Carvalho; Grunspun, Henrique; Bueno, Marco Aurelio Scarpinella (Frontiers in Nutrition, 2022)
Introduction: Bioethics and nutrition are essential issues in end of life, advanced dementia, life-sustaining therapies, permanent vegetative status, and unacceptably minimal quality of life. Even though artificially administered nutrition (AAN), for this type of health condition, does not improve quality of life and extension of life, and there is evidence of complications (pulmonary and gastrointestinal), it has been used frequently. It had been easier considering cardiopulmonary resuscitation as an ineffective treatment than AAN for a healthy team and/or family. For this reason, many times, this issue has been forgotten. Objectives: To discuss bioethical principles and AAN in these patients. Discussion: The AAN has been an essential source of ethical concern and controversy. There is a conceptual doubt about AAN be or not be a medical treatment. It would be a form of nourishment, which constitutes primary care. These principles should be used to guide the decision-making of healthcare professionals in collaboration with patients and their surrogates. Conclusions: This difficult decision about whether or not to prescribe AAN in patients with a poor prognosis and without benefits should be based on discussions with the bioethics committee, encouraging the use of advanced directives, education, and support for the patient, family, and health team, in addition to the establishment of effective protocols on the subject. All of this would benefit the most important person in this process, the patient.